(untitled) (Research, Society and Development, 2022)
Objective: The objective of this study is to establish the importance of the E-learning system in health sciences as well as the impact that it generated due to the COVID-19 pandemic. Methodology: An exhaustive search strategy of the scientific literature was carried out using the PUBMED database, through the keywords "E-Learning", "Health Sciences" and " COVID-19", where a total of 20 scientific articles could be obtained. Results: E-learning education represented a fundamental tool to be able to fulfill several objectives of health sciences, however, there appeared several advantages and disadvantages during its execution. Conclusion: The usefulness of E-learning in the context of the COVID-19 pandemic was of great importance for the health sciences. However, based on this experience, several parameters can be established to take into account to improve and explore various fields of this educational system.